Formation of ecological culture of students – the basis of a healthy lifestyle - Джанзакова, Шолпан; Базаргалиев, Ғабит; Шәпиева, Мейрамгүл; Кайдарова, Аймен (Pedagogy and Psychology, 2020)
The methodological and practical importance of determining the characteristics of the formation of the ecological culture of students is studied in this article based on the provisions and requirements of the main documents of the state as well as the works of scientists. From the conclusions on environmental upbringing, it is clearly formulated that a person should serve consciously to protect the natural environment in the search for effective ways to maximize the reproduction of natural resources, eliminate the negative changes that occur in the natural environment and improve the system of environmental education. The possibility of environmental upbringing in the main areas of the formation of a person’s love for nature on the basis of national customs, proverbs, sayings, riddles, prohibitions, ceremonies is provided. Generally, the universal ecological system as a continuous system of education and upbringing, based on the mastery of skills and knowledge related to the environment, the formation of a cultural environment as a result of influencing the consciousness and worldview of a person including mercy, charity and natural beauty has a huge impact on the development of a spiritual quality personality.